2004
DOI: 10.1007/s11745-004-1269-4
|View full text |Cite
|
Sign up to set email alerts
|

A short, concise route to diphosphatidylglycerol (Cardiolipin) and its variants

Abstract: A new approach is described for the synthesis of the cardiolipin family of phospholipids that uses phosphonium salt methodology. The method involves the reaction of 2-O-protected glycerol with a trialkyl phosphite derived from 1,2-diacylsn-glycerol in the presence of pyridinium bromide perbromide and triethylamine to afford the phosphoric triesters. The synthesis involves three steps and allows the preparation of a wide range of cardiolipins with different substitution patterns and chain lengths, including uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Other synthetic approaches describe the use of phosphorylating agents such as cyclic enediol pyrophosphates [6][7][8], silver salts of PA [9,10], phosphorus oxychloride [11], and 2-chlorophenyl phosphorodi-(1,2,4-trizolide) [12]. As part of our ongoing research towards the synthesis of cardiolipin and its analogues, we have developed and reported convenient alternative methodologies [13][14][15] based on phosphoramidite chemistry [16,17]. However, all these methods utilize 2-O-protected glycerols along with the phosphorylation or condensation reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Other synthetic approaches describe the use of phosphorylating agents such as cyclic enediol pyrophosphates [6][7][8], silver salts of PA [9,10], phosphorus oxychloride [11], and 2-chlorophenyl phosphorodi-(1,2,4-trizolide) [12]. As part of our ongoing research towards the synthesis of cardiolipin and its analogues, we have developed and reported convenient alternative methodologies [13][14][15] based on phosphoramidite chemistry [16,17]. However, all these methods utilize 2-O-protected glycerols along with the phosphorylation or condensation reagents.…”
Section: Introductionmentioning
confidence: 99%